Eastwood's Iwo Jima : critical engagements with Flags of our fathers and Letters from Iwo Jima - Schubart, Rikke, 1966-; Gjelsvik, Anne, 1965- (Wallflower Press, 2013)
With Flags of Our Fathers (2006) and Letters from Iwo Jima (2006), Clint Eastwood made a unique contribution to film history, being the first director to make two films about the same event. Eastwood's films examine the battle over Iwo Jima from two nations' perspectives, in two languages, and embody a passionate view on conflict, enemies, and heroes. Together these works tell the story behind one of history's most famous photographs, Leo Rosenthal's "Raising the Flag on Iwo Jima." In this volume, international scholars in political science and film, literary, and cultural studies undertake multifaceted investigations into how Eastwood's diptych reflects war today. Fifteen essays explore the intersection among war films, American history, and Japanese patriotism. They present global attitudes toward war memories, icons, and heroism while offering new perspectives on cinema, photography, journalism, ethics, propaganda, war strategy, leadership, and the war on terror.